Spatio-temporal Analysis of Drought Trends Recorded during the Wettest Months in the Mouhoun-Comoé Basin in Burkina Faso (Africa): an Analysis using Z-score and Linear Regression - Yameogo, Joseph (Geographica Pannonica, 2025)
Meteorological drought is a natural phenomenon that occurs when there is insufficient rainfall over a more or less prolonged period. In West African countries, and particularly in Burkina Faso, this situation undermines agricultural systems. Knowledge of the spatio-temporal trends of drought is essential for optimal management of water resources and effective planning of sustainable agricultural activities. The aim of this study is the analysis of the spatio-temporal trends of drought in the Mouhoun-Comoé basin in Burkina Faso. To this end, the study used CHIRPS rainfall data in raster and CSV file form for July and August, as well as soil moisture (0-10 cm) at 1-, 2- and 3-month scales for the period 1994-2024. The data were analysed using the z-score index, linear regression and correlation. The study shows that the upward trend in drought oscillates between extreme drought and mild drought. The decade 1994-2004 was characterised by extreme drought, followed by a decrease in drought throughout the basin during the decade 2005-2014. Finally, in the decade 2015-2024, a phase of high humidity was observed throughout the basin. Drought trends have had an impact on soil moisture levels, particularly in the valleys of the basin. This situation has a negative impact on agricultural production in the basin. This situation is forcing farmers to use crops that have more or less water tolerance in order to cope with the drought.